What do we know about experiencing the end-of-life in burn intensive care units? a scoping review - Ribeiro, André Filipe (2022)
Objectives: To review and synthetize the evidence on end-of-life in burn intensive care units about (i) the characteristics of end-of-life in burn intensive care units, (ii) the symptom control provided to burned patients facing dying and death in this context, and (iii) the concept, models and designs of the care provided. Methods: Systematically conducted scoping review, following Arksey and O'Malley's framework. Preferred Reporting Items for Systemic Reviews extension for Scoping Reviews was used as a reporting guideline. Searches were performed in three databases, with no time restriction and up to September 2021. Results: 16,287 documents identified; thirteen (13) selected for analysis and synthesis. Three key themes emerged: (i) characteristics of the end-of-life in burn intensive care units, including end-of-life decisions, decision-making processes, causes and trajectories of death; (ii) symptom control at the end-of-life in burn intensive care units focusing on patients’ comfort; and (iii) concepts, models, and designs of the care provided to burned patients at the end-of-life, mainly care approaches, provision of care and palliative care.Significance of Results: End-of-life care is a major step in the care provided to critically ill burned patients. Dying and death in burn intensive care units are often preceded by end-of-life decisions, namely forgoing treatment, and do-not-attempt to resuscitate. Different dying trajectories were described, suggesting the possibility to develop further studies to identify triggers for palliative care referral. Symptom control was not described in detail. Palliative care was rarely involved in end-of-life care for these patients. This review highlights the need for early and high-quality palliative and end-of-life care in the trajectories of critically ill burned patients, leading to an improved perception of end-of-life in burn intensive care units. Further research is needed to study the best way to provide optimal end-of-life care and foster integrated palliative care in burn intensive care units.